EXPLORING COACH PERCEPTIONS OF YOUTH SPORT SPECIALIZATION: A COMPARISON OF THE HIGH SCHOOL AND CLUB SPORT CONTEXTS. Issue 3 (31st March 2019) - DiSanti, Justin S.; Post, Eric G.; Bell, David; Schaefer, Dan; Brooks, M. Alison; McGuine, Timothy A.; Erickson, Karl T.
BACKGROUND: A recent focus of the literature that has bridged the sports medicine and sport psychology domains relates to the topic of youth sport specialization. Previous work has identified specializing in one sport – particularly at an early age – to be associated with increased risks of negative physical (i.e., overuse injuries, lower extremity injuries) and psychosocial outcomes. As a result, medical organizations have advocated for a more diversified, multisport experience. Despite these recommendations, concerns regarding the rising prevalence of sport specialization have been a continued fixture of the literature, with little known regarding how underlying attitudes, beliefs, and values of sport stakeholders may be shaping this trend. One proposed avenue for better understanding this gap between recommendations and perceived participation behaviors is to examine and compare the club and high school sport contexts. Specifically, club sports have been linked to more professionalized climates of competition, in turn suggesting that specialization may be viewed more favorably than in the high school setting. Therefore, the purpose of the current study was to examine the perceptions of coaches in the high school and club sport contexts related to youth sport specialization to better understand how these youth sport leaders compare in their endorsement of attitudes and behaviors promoting this phenomenon. METHODS: This cross-sectional study examined 769 currently-practicing coaches (497 high school, 272 club; 533 male, 266 female). Participants completed a novel perceptual measure which surveyed their attitudes, values, and beliefs related to various aspects of youth sport specialization (e.g., effectiveness in developing talent, likelihood of leading to an enjoyable experience, likelihood that their competition specializes). The participant's mean rating across the 25 items denoted their global perception of sport specialization (i.e., higher scores indicated a more favorable view of specializing). Additionally, each coach completed a questionnaire detailing their relevant demographic and sport background information. To analyze the data, an independent samples t-test was conducted between the two groups while using their perceptual score of specialization as the dependent variable. Finally, a multiple linear regression was calculated separately for each coach group to predict participants' perceptual scores of specialization based on their demographic and sport background responses (i.e., age of athletes coached, years of experience as a coach, post-secondary education in sport, additional coaching certifications, self-rating of coaching quality). RESULTS: High school coaches (M = 2.31; SD = 0.21) and club coaches (M = 2.43; SD = 0.25) differed in their average perceptions of sport specialization (t(767) = 1.412; p < .001), meaning that the club sport coaches were more likely to rate specialization as a positive, adaptive practice in comparison to their high school counterparts. For high school coaches, the overall regression equation was significant, but explained only a small amount of variance (F(5, 491) = 2.542, p = .028, R2 = .025); however, no demographic characteristics were strong independent predictors. The multiple linear regression for the club coaches did not yield a significant equation to predict perceptual scores of specialization based on their sport background characteristics (F(5, 256) = .224, p = .952, R2 = .004). SIGNIFICANCE: This study was the first to examine sport specialization by comparing the high school and club sport contexts. These findings indicate that club sport athletes are more likely to be exposed to messaging and attitudes that posit sport specialization as favorable, despite the proliferating base of evidence detailing the physical and psychosocial risks of this pattern. Additionally, the multiple linear regression analyses specify that elements of coach education, experience, and demographic characteristics do not strongly predict perceptions of specialization, suggesting that the competitive contexts themselves (high school vs. club) may be the most salient influencer of these perceptions. Therefore, club sports appear to be a critical point-of-impact for a cultural shift to better account for the potential drawbacks of specializing in one sport stemming from previous sports medicine literature. Athletes in these contexts should also be aware of the heightened expectation of specialized participation by those leading their teams. Pediatric sport researchers and practitioners should continue to explore how these differing group perceptions manifest in terms of participation behaviors, as well as their link to overall athlete health, well-being, and development.